Produksi Antibodi Monoklonal Untuk Deteksi Virus Tungro Terbawa Vektor - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2001)
Abstract Tungro is the most important rice viral disease. The disease is transmitted by leafhoppers semi persistently. The most efficient vector is Nephotsttix virescens Distant. The objective of the following studies were to produce monoclonal antibody against RTV which could be used detection RTV in the viruliferous N. virescens and to determine its retension using non precoated I-ELISA. The results showed that fusion of NS-1 myeloma cell with lymphocite cell of Balb/c mouse produced four antibody clones (AbMTl, AbMT2, AbMT3, and AbMT4) with average antibody titer of 10" and the antibody clones were IgM and Ig G2a AbMT3 was better than the other in its reaction and then used for following assays. Optimum dilution of antigen and antibody for non precoated indirect ELISA were 102 and 101. RTV could be detected from single viruliferous green leafhopper. The highest RTV concentration in the viruliferous vector was three days after acquisition feeding and than decreased in the next following day.